Application of the chaotic power law to the study of cardiac dynamics in patients with arrhythmias (2014)
Background. An exponential law for chaotic cardiac dynamics, found previously, allows the quantification of the differences between normal cardiac dynamics and those with acute diseases, as well as the cardiac dynamics of the evolution between these states.Objective. To confirm the clinical applicability of the developed methodology through the mathematical law for cardiac dynamics in dynamics with arrhythmias.Materials and methods. 60 Holter electrocardiograms were analyzed, 10 corresponded to normal subjects, and 50 to subjects with different arrhythmias. For each Holter, an attractor was performed, and its fractal dimension and spatial occupancy were measured. A mathematical evaluation was applied in order to differentiate normal dynamics from pathological ones. Sensitivity, specificity and the Kappa coefficient were calculated.Results. The mathematical evaluation differentiated occupation spaces, normal dynamics, acute illness dynamics, and evolution between these states. The sensitivity and specificity values were 100%, and the Kappa coefficient was 1.Conclusions. The clinical applicability of the methodology for cases with arrhythmia was shown. It is also applicable for the detection of changes in dynamics that are not classified clinically as pathological.